Impact of Coronary Artery Bypass Graft on left Ventricular Systolic Function - Dilshad Abdulqadir Rasul; Mohammed Hasan Alwan (Advanced Medical Journal)
Background& objective: Coronary artery disease is the common cause of disease-specific mortality and morbidity in Iraq. The objective was to evaluate the effect of coronary artery bypass graft surgery on left ventricular systolic function.